EFFECT OF ERRQ STRATEGY FROM TEXT TYPES BY EIGHTHGRADE STUDENTS’ READING COMPETENCY - Luh Widiani (Sekolah Tinggi Pariwisata Mataram, 2021)
The problems were focused on the following, they are: 1) the main effect of scientific approach combined with ERRQ strategy on the eighth graders’ reading competency, 2) the differences of the effect of scientific approach combined with ERRQ strategy viewed from text types on the eighth graders students’ reading competency. The research methods were the following. The population included students at SMP Santo Yoseph Denpasar. The sample were recruited from the eighth grade of SMP Santo Yoseph Denpasar. They were recruited using a Random Sampling. Data were collected by means a Posttest. The obtained data were analyzed by means of One-Way ANOVA. The results show the following: 1) there is a significant effect of scientific approach combined with ERRQ strategy on the students’ reading competency which total mean score (X: 77.27) (λ: 0.01); 2) The differences of the effect of scientific approach combined with ERRQ strategy viewed from text types on the students’ reading competency could be arranged consecutively as follows: narrative text (X76.47), recount text (X:78.78), descriptive text (X: 76.83).